(untitled) (Journal of the College of Education for Women, 2019)
The purpose of this study is to show the constants and variables geography in Russianpolicy in light of variables geostrategic witnessed by the world, especially after the collapseof the Soviet Union and the disintegration to fifteen Republic became the Russian Federationand the heir to the Soviet Union, Geography particularly important because the impact of itsdata in policy making less change ofothers, and explain the political choices cannot achievesecurity through its relationship constants geographical (natural or human) paint forms ofeconomic activity and determine the points they national security. issue is the geographicalthis or that country is determined by its policy also specifies the way in which thinks policymakers by the short-termand long term. here comes the importance of the study to analyzeand detect the strengths and weakness in the Russian Federation and its impact on policymakingand what is the role that can be played on the stage of international politics and inparticular the Arab world.